Effectiveness of Providing Educational Information Counseling (IEC) Related to Diabetes Mellitus Type 2 to the Community of Sungaibuntu Village, Karawang Regency: Efektifitas Pemberian Konseling Informasi Edukasi (KIE) Terkait Diabetes Mellitus Tipe 2 Kepada Masyarakat Desa Sungaibuntu Kabupaten Karawang - Dian Agnesa Sembiring; Iha Nursolihah (JOHAR (Journal of Hospital Administration Research), 2024)
Diabetes mellitus (DM) is a metabolic disease that is increasingly preval_ent in the global community, including in Indonesia. In Sungaibuntu Village, the preval_ence of obesity and hypertension is quite high, while the community still lacks understanding and awareness of the dangers and early symptoms of DM. Therefore, an appropriate Information Education Counseling (IEC) program is essential to increase community knowledge and awareness, so that they can actively participate in maintaining their health. This study was a descriptive observational study with a one group pretest-posttest research design conducted on the community of Sungaibuntu Village, Karawang Regency, with a sample of 71 people selected by purposive sampling. Research data were collected using a questionnaire related to community knowledge about DM, and the data were analyzed using descriptive statistics and independent sample T-test. The results showed a significant change in knowledge between before and after the IEC treatment. In addition, the IEC proved to be effective in increasing respondents' knowledge about DM. Hopefully, the results of this study can be an input in efforts to prevent and control DM for the participants